La résidence aristocratique de Montmartin (Oise) du IIIe au IIe s. av. J.-C. - Brunaux, Jean-Louis; Meniel, Patrice (Documents d'archéologie française, 1997)
Construction work on the TGV Nord railway discovered the exceptional gaulish site of Montmartin/La Fosse Muette. A rich aristocratic dwelling was uncovered and the abundance of small finds shows the diversity of the craft activities (metal working, pottery production...). In addition, a public and religious space was observed, composed of a small temple, similar to the famous site of Gournay-sur-Aronde, along with an attached public square or meeting place. This represents a first-rate document for the religious practices (notably for the treatment of corpses) and the gaulish warrior society, that of the equites described by Caesar.